Arbuscular mycorrhizae alleviate water deficit in Dipteryx alata Vogel: seedling quality and resilience - Jesus, Maílson Vieira; Scalon, Silvana de Paula Quintão; Dresch, Daiane Mugnol; Linné, Jéssica Aline; de Lima, Vânia Tomazelli [UNESP]; Reis, Lucas Coutinho; Santos, Cleberton Correia; Foresti, Andressa Caroline (Canadian Science Publishing, 2022)
Dipteryx alata Vogel (Fabaceae) is a fruit tree species native to the Cerrado with ecological and economic potential. However, a water deficit can be a limiting factor to the initial growth of this species, requiring knowledge on technologies that can alleviate this stressful effect. We hypothesized that inoculation with arbuscular mycorrhizae fungi contributes to stress mitigation during and after water deficit. Dipteryx alata seedlings were subjected to two water regimes (control: seedlings irrigated daily; and water deficit: irrigation suspension), associated with inoculation with arbuscular mycorrhizal fungi (AMF) (AM–, without inoculation; AM+, inoculation with Rhizophagus clarum), and three evaluation periods (T0, time zero; F0, zero photosynthesis (7 days of water restriction); REC, recovery (100 days)). Water deficit impaired water relations, decreasing the quality of D. alata seedlings. AM+ seedlings showed higher relative water content (RWC), leaf area ratio, chlorophyll index, and Rubisco carboxylation capacity (A/Ci), which helped in photosynthetic metabolism. Inoculation with R. clarum alleviated the impact of stress on water use efficiency, water potential, RWC, and A/Ci in REC. Inoculation with AMF is a promising management technique in the production of D. alata seedlings for increasing seedling quality and resilience to water deficit.
Keywords: Arbuscular mycorrhizal fungi; Baru; Greenhouse experiment; Hydrical stress; Rhizophagus clarum